When pulmonary embolism is not an obvious diagnosis - pathophysiology, risk factors, diagnosis, treatment and a review of the most unusual cases - Kozakiewicz, Julia; Okońska, Aleksandra; Kościelecki , Kamil; Kalisz, Agnieszka; Mączewska, Klaudia; Skorulska, Iwona; Długozima, Patrycja; Głowacka, Aleksandra; Grywińska, Weronika; Grzeszczuk , Paulina (Quality in Sport, 2025)
Introduction: This review paper aims to emphasize how pulmonary embolism is a seriously life-threatening disease entity, point out risk factors, symptoms, diagnostic trails, treatment and prove that a diagnosis, specifically aimed at embolism is often not obvious in given clinical cases. Materials and methods: A review of chosen literature in the PubMed database was conducted, using the following keywords: , pulmonary embolism”, , vein thrombosis’’, , thrombosis risk factors”, , anticoagulation”. Summary: Pulmonary embolism is a dangerous disease that can lead to serious complications and death, if not properly diagnosed and treated. Proper diagnosis is crucial, as symptoms can be uncharacteristic and embolism can occur in a variety of configurations. Prompt implementation of treatment, including the use of anticoagulants, as well as appropriate medical care, can significantly improve patients’ prognosis. Conclusions: Lesser-known risk factors for pulmonary embolism include sepsis, urinary retention, hematologic, rheumatic and endocrine diseases, organ transplants, treatment with bone cement or tranexamic acid. It is important to conduct diagnostic testing for pulmonary embolism when characteristic symptoms occur and introduce appropriate therapy as well as thromboprophylaxis depending on the patient’s risk and clinical condition.